Strain-Stress State of Wood During Drying Process - V. A. Sychevsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes theoretical and experimental methods for investigation of strain-stress state of wood and lumber saw-timbers in the process of heated-air drying.